Fire hazards in industry - Thomson, Norman G. (Elsevier, 2001)
Significant loss to business occurs through fires in the workplace. Fire legislation has changed over the years, especially with the introduction of the European Directives. Designed to cover, in general terms, exactly what is required of employers, this book considers the basics of good fire safety management.
Keywords: Fire prevention -- Law and legislation.; Fire risk assessment.; Fire prevention -- Management.; elektronické knihy; electronic books